Deixis Analysis in the Song Lyrics of Cancer by My Chemical Romance - Martin Panji Perdana; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the use of deixis in the lyrics of "The Black" by Imminence, focusing on types of deixis such as person, spatial, and temporal deixis. Deixis is a linguistic phenomenon that connects language to the context of an utterance, allowing meaning to be constructed based on the speaker’s position, the listener, time, and place. The findings show that person deixis is the most dominant type found in the song lyrics (78,13%), followed by spatial deixis ((9,38%), and temporal deixis (12,5%). The dominance of person deixis indicates that the lyrics emphasize emotional expression and the songwriter’s personal experiences. This study highlights the importance of deixis in revealing the relationship between linguistic context and meaning in musical art.